Impaired megakaryopoiesis and behavioral defects in mafG-null mutant mice - Shavit, Jordan A. (Cold Spring Harbor Laboratory Press, 1998)
The small Maf proteins (MafG, MafK, and MafF), which serve as heterodimeric partner molecules of CNC family proteins for binding in vitro to MARE sites, have been implicated in the regulation of both transcription and chromatin structure, but there is no current evidence that the proteins fulfill these functions in vivo. To elucidate possible contributions of the small Maf proteins to gene regulation, we have ablated the mafG and mafK genes in mice by replacing their entire coding sequences with the Escherichia coli lacZ gene. mafG homozygous mutant animals exhibit impaired platelet formation accompanied by megakaryocyte proliferation, as well as behavioral abnormalities, whereas mafK-null mutant mice are phenotypically normal. Characterization of the mafG and mafK embryonic expression patterns show that their developmental programs are distinct and intersecting, but not entirely overlapping. These results provide direct evidence that the small Maf transcription factors are vital participants in embryonic development and cellular differentiation.